IDENTIFICATION OF CHILD-FRIENDLY NEIGHBORHOOD PARKS AROUND THE INDUSTRIAL AREA IN THE SUB-DISTRICT OF CAKUNG, EAST JAKARTA - Ranuna Yonestra Nugraha; Rahel Situmorang; Silia Yuslim (Journal of Synergy Landscape, 2024)
Cakung sub-district has the largest population of children aged 0–18 years compared to other sub-districts in East Jakarta. Children need space to play. This space is important for child development. Neighborhood parks developed in residential areas are used as places for children to play. Empirical conditions show that neighborhood parks in Cakung District are not qualified the standard of safe distance from industrial activities. The existence of industrial activities and mobility poses many safety and health hazards for children. With the conditions that occur, neighborhood parks, as open spaces closest to where children live, can still be a place for children to play. This study aims to identify the quality of neighborhood parks around industrial areas in Cakung District based on child-friendly criteria. The method used is scoring analysis with the main assessment parameters related to industrial areas and supporting assessment parameters related to the completeness of child-friendly parks, spatial analysis, and quantitative descriptive analysis. The results of this study, which obtained eight neighborhood parks are not qualified the criteria for being child-friendly using the main research parameters. The parks that are not child-friendly are Taman Metland Menteng, Taman PIK, RPTRA Pulo Indah, Taman Casia, RPTRA Menteng Asri, RPTRA Sangkuriang, Taman Yukayuh Metland, and RPTRA Cakung Timur. Then, for the assessment related to the completeness of the park, the results obtained from the RPTRA-type park already have completeness facilities in accordance with child-friendly criteria, while the non-RPTRA park has inadequate garden completeness. Improving the quality of neighborhood parks around industrial areas can be done with a design approach and adding park facilities.